Opinions of professors, dental students, and patients for publishing the patient images in the articles - Ava Rowshani; Maryam Alsadat Hashemipour (BMC, 2024)
Abstract Introduction The journals must have an instruction for writers to observe the essential ethical principles like privacy-preserving, secrecy, and keeping the patients' identities hidden. Even though patient secrecy is an important ideology in medicine's ethics, most journals have a little guide on this topic for the authors. According to the absence of such studies in dentistry and limited studies in medicine, our goal in this article is to review the opinions of professors, Kerman dentistry students, and patients for publishing the patient images in the articles. Method This research is an analytical, sectional, and descriptive study. The studied society includes the professors of the dentistry faculty (54 people), the 4th to 6th years dentistry students (122 people), and 129 patients who referred to the offices, the faculty, and other clinics in Kerman city base on simple random sampling method. A query including the personal questions, and questions related to the participants' opinions about publishing the images was given to contributors. Abundance, average tables, chi-square (χ 2) test, T-test, and SPSS 21 software were used for data description. Results The contributors' attitudes were different in three groups of participants: more than half of the patients (58.91%), 39.5% of students, and 31.38% of professors believed that no permission is needed. While, 64.34% of the patients, 89.34% of students, and 83.3% of professors believed that written permission is needed for publishing. Conclusion From the participants' viewpoints, more strict forms are needed by increasing identity recognizability. The professors are more eager than the patients to receive patients' permission for any kind of image. By reducing the level of identification, doctors and students are more eager than patients to receive approvals.